Radioecological research of the city Karakol of Issyk-Kul region (Eurasian Journal of Ecology, 2020)
The main criterion for the Issyk-Kul region is the balanced socio-economic development of the region, compliance with environmental standards in order to preserve biodiversity, landscapes and naturalecosystems. The city of Karakol is the administrative and cultural center of the Issyk-Kul region, ensuringradioecological safety is a prerequisite for the quality of the environment for the sustainable development of the region. The purpose of the work is a radioecological assessment of the environment of thecity of Karakol. The exposure dose rate of the background radiation was determined by the methodof pedestrian gamma-survey, the specific activity of radionuclides in the soil was determined by thegamma-spectrometric method of analysis. Erica tool 1.3 software was used for absorbed dose levels andassessment of radiation risks. According to the research results, it was found that the level of the exposure dose of gamma radiation does not exceed the permissible norm and varies in the range of 16-25μR / h. The specific activity of radionuclides in the soil (238U, 232Th, 40K, 137Cs) is within natural values,the absorbed dose level and radiation hazard coefficients do not pose a threat to living organisms. Theobtained research results significantly supplement the databases of radioecological monitoring of naturaland technogenic ecosystems in Kyrgyzstan and are of great value for the nature protection structures ofthe region.Key words: radiation background, radionuclide, soil, specific activities